A RAG1 and RAG2 Tetramer Complex Is Active in Cleavage in V(D)J Recombination - Bailin, Tu (American Society for Microbiology, 1999)
During V(D)J recombination two proteins, RAG1 and RAG2, assemble as a protein-DNA complex with the appropriate DNA targets containing recombination signal sequences (RSSs). The properties of this complex require a fairly elaborate set of protein-protein and protein-DNA contacts. Here we show that a purified derivative of RAG1, without DNA, exists predominantly as a homodimer. A RAG2 derivative alone has monomer, dimer, and larger forms. The coexpressed RAG1 and RAG2 proteins form a mixed tetramer in solution which contains two molecules of each protein. The same tetramer of RAG1 and RAG2 plus one DNA molecule is the form active in cleavage. Additionally, we show that both DNA products following cleavage can still be held together in a stable protein-DNA complex.